The Effect of Self-Efficacy and Social Skills on Science Learning Outcomes for Junior High School Students in Jember Regency - Bektiarso, Singgih; Sudarti; Wicaksono, Iwan (Advances in Social Sciences Research Journal, 2022)
The purpose of this study was to examine the effect of self-efficacy and social skills simultaneously and partially on science learning outcomes for junior high school (SMP) students in Jember Regency. This research is a type of causality explanatory research, namely research that intends to explain the effect of the independent variables on the dependent variable. The data analysis technique used is statistical test with multiple linear regression test technique using SPSS version 25 statistical application. The results of the normality test for the variable data are self efficacy (X1) sig 0.2> 0.05, social skills (X2) sig 0.2> 0.05, and science learning outcomes (Y) sig 0.178>0.05, thus the data variance of all variables is normally distributed. Thus, data analysis with multiple linear regression test techniques can be continued. Based on the results of the regression analysis, it was found that 1) hypothesis testing there was a significant effect of self-efficacy and social skills on students’ science learning outcomes simultaneously obtained sig 0.000, meaning that this number was below 0.05, thus the null hypothesis was rejected; 2) hypothesis testing that there is a significant effect of self-efficacy on students’ science learning outcomes partially obtained sig 0.023, meaning this number is below 0.05, thus the null hypothesis is rejected; 3) hypothesis testing that there is a significant effect of social skills on students’ science learning outcomes partially obtained 0.003 meaning this number is below 0.05, meaning the null hypothesis is rejected. Based on this description, it can be concluded that self-efficacy and social skills have a significant effect simultaneously and partially on science learning outcomes for junior high school students in Jember Regency.